Viscosity of molten CaOK2OSiO2 woody biomass ash slags in relation to structural characteristics from molecular dynamics simulation. (6th April 2020) - Ma, Charlie; Skoglund, Nils; Carlborg, Markus; Broström, Markus
Highlights: MD simulations of molten slags correlated structural characteristics with viscosity. SiOSi angles between adjacent silicate tetrahedral units increase with viscosity. Bond lengths between Si and bridging O atoms decrease with increasing viscosity. K and Ca affect network structure and atomic mobility to different extents. Depolymerization and diffusivity influences the silicate network structure. Abstract: Molten compositions in the CaOK2 OSiO2 system relevant to woody biomass ash slags were simulated with molecular dynamics to extract structural characteristics. Multivariate analysis elucidated correlations of these structural characteristics with viscosity measurements. The simulations show SiO4 /silicate tetrahedral units (STUs) diffusing slowly and forming flexible networks via oxygen bridges. The degree of STU polymerization varies linearly with the (K2 O + CaO)/SiO2 ratio. Ca depolymerises stronger than K, but K diffuses quicker. Depolymerization and diffusion cause network disruptions and agitations that promote collective atomic mobility of the system. This imposes structural characteristics in the slag that correlate with viscosity. The inter-STU SiOSi angle narrows with decreasing viscosity, while the SiO bond length of these bridges increases. Attributes related to atomic mobility, such as the variations in the SiOSi angle and the distance of nearest SiSi pairs, also correlate with viscosity. The discussion provides insight into the connection between structural characteristics and viscosity.